Integration and the economy. Silesia in the early modern period - Goliński, Mateusz (Publishing House eBooki.com.pl, 2014)
Despite having distinct features due to economy, Silesia was no different, in context of events shaping conditions of development, from the neighbouring regions, especially the Bohemian Crown from the 16th to the 18th centuries. The particular interests of the Silesian economy since the 17th century were required, possibly enabled by the political distinctiveness of the region and the complex structure of the monarchy. Also relevant were strong external relations (transit, export and import) long maintained despite divisions, both political and at customs. Said „interests” could themselves be considered an additional factor integrating the region, (certainly, that became so in time) if not for their existence stemming from earlier political integration and specifically being an unexpected (since mercantile times intentional) result of the “external” factor, specifically state politics. Although lacking the influence it enjoyed in earlier times, Wrocław remained the primary beneficiary, as its economic interests were typically considered synonymous with interests of entire Silesia.
Keywords: 16th-18th centuries; tariff policy; tax policy; Silesia; economic policy; communication; Silesia